Polysaccharides from Nature to Technology: Grafting Techniques and their Applications - Mahajan, Hitendra; Suryawanshi, Meghraj; Sarode, Rahul; Gujarathi, Pranjal (Current Applied Polymer Science, 2025)
Polysaccharides, naturally occurring and renewable biopolymers, have garnered significant attention due to their structural versatility and wide-ranging applications across the biomedical, pharmaceutical, and industrial sectors. This review explores the role of polysaccharides as excipients and their emerging importance in drug delivery systems, gene therapy, tissue engineering, medical implants, and biosensing. With detailed insights into their antioxidant, anti-inflammatory, and anticancer properties, the review highlights the significance of polysaccharides, such as chitosan, alginates, cellulose, hyaluronic acid, pullulans, and xanthan gum, in developing advanced biomaterials. Various grafting techniques, including chemical and physical methods, are examined for their potential to modify surface properties and enhance biocompatibility, targeting ability, and mechanical strength. Despite the promising biomedical applications, challenges persist in optimizing grafting techniques, ensuring biocompatibility, and overcoming regulatory hurdles. This review also enlightens the current market potential of polysaccharides, emphasizing the growing demand for natural and plant-based materials. Future directions should focus on enhancing the scalability of production, improving chemical modification processes, and addressing technical limitations in tissue engineering applications.
Keywords: nature to technology